Sistem Pengambilan Keputusan Dalam Pemilihan Karyawan Terbaik : Literature Review - Pupu Pujiawati; Vip Paramarta; Gregorius Yoga Panji Asmara (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
The company is an institution or organization that provides goods or services, the purpose of which is to get result or profits. In the company there are human resources who work to carry out company activities, the company to carry out evaluations including evaluating the best employees for the purpose of being rewarded at work. However the implementation of the company is constrained by the best employee evaluation system. Therefore, a decision making system is a needed to accelerate the assessment of the best employees. Decision support system (DSS) is a type of decision making system that assists decisions in making decision by providing the required data, information and knowledge. Decision support system (DSS) can combine internal and external data, perfrom analysis and provide recommendations. This literature source was taken from sources, namely PubMed, Google Scholar and ProQuest. Using eyword : “ decision making system” or “ decision support system”, “election” or “selection”, “the best employee”. Get 8 articles that fit to into the inclusion criteria. 8 articles were included in this review.